The Impact of Green Talent Management on Employees' Innovative Work Behavior: The Mediating Role of Transformational Leadership - An Applied Study on Construction Companies in Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to investigate the impact of green talent management on employees' innovative work behavior. It also sought to analyze the role of transformational leadership in mediating the effect of green talent management on employees' innovative work behavior within construction companies in the Kingdom of Saudi Arabia. The study utilized a descriptive-analytical approach, with a convenience sample of 281 individuals from supervisory and managerial positions. A questionnaire was used as the data collection tool to test the study hypotheses and answer its research questions. The study's findings revealed that both soft and hard green talent management have an effect on employees' innovative work behavior. Transformational leadership also has an effect on employees' innovative work behavior. Additionally, there is an effect of both soft and hard green talent management on transformational leadership. The study recommended leveraging talented and experienced individuals by sending them to training programs to acquire additional skills and expertise. This would enable them to complete and accomplish tasks in innovative ways, thereby fostering innovative work behavior among employees.
Keywords: Green Talent Management; Employees' Innovative Work Behavior; Transformational Leadership; Construction Companies in the Kingdom of Saudi Arabia